Toward spatial justice: The spatial equity effects of a toll road in Cape Town, South Africa - van Dijk, Justin Tycho; Krygsman, Stephan; de Jong, Tom (Journal of Transport and Land Use, 2015)
The present study sets out to provide an ex ante insight into the equity effects of a toll charge on the traffic diversions and geographical accessibility of work locations in the Cape Town metropolitan region, South Africa. Based on a static traffic assignment model and aggregate accessibility measures, computed in a GIS environment, the effects of a toll were estimated for different income categories for both a reference scenario and two toll scenarios. The findings indicate that particularly low-income commuters will divert to alternative routes. However, the results also indicate that the introduction of a toll will only have a limited impact on geographical accessibility. Nevertheless, because particularly low-income commuters are likely to divert to alternative routes, a toll should maybe not be levied on the road toward spatial justice without revenue redistribution or additional investment in the public transport system.